PENGARUH MULTIMEDIA INTERAKTIF PADA KEMAMPUAN PENGAJARAN MENDENGARKAN SISWA KELAS DELAPAN MTs AL-FATWA - Irawati; Nizarrahmadi; Alvina Yolanda; Dewi Ismu Purwaningsih (Pengelola Jurnal Politeknik Negeri Ketapang, 2025)
This study aims to determine whether interactive multimedia that teaches listening skills can affect students' listening scores in eighth- grade students of Mts Al-Fatwa. The research design used is Quasi- Experimental. The population of this study was all Mts Al-Fatwa students, and the sampling used the eighth grade which amounted to 28 students. Pre-test and post-test were the tools utilized to gather data. An independent t-test was used to statistically examine the pre-test and post-test data. The conclusion on the independent t-test is 3.992 > 1.701. So H0 is rejected and HA is accepted because the t-count is greater than the t-table.